Hubungan Pengetahuan Tentang Gizi Ibu Hamil dengan Kekurangan Energi Kronis Pada Ibu Hamil di UPT Puskesmas Anuntodea Tipo - Aisa T. Hasan; Masri Dg Taha; Benny Harry L. Situmorang (Universitas Pahlawan Tuanku Tambusai, 2024)
Nowadays, Chronic Energy Deficiency (CED) in pregnant women has become a common problem. Pregnant women suffer from a nutritional deficiency for a long time, which could affect their health and lead to Low Birth Weight in babies. The aim of the study is to determine the correlation between knowledge about the nutrition of pregnant women and chronic energy deficiency in pregnant women in Anuntodea PHC, Tipo. This research uses quantitative analytical research methods with a cross-sectional research design. The samples were taken using the purposive sampling technique, with a total sample of 50 respondents. Data were collected by using the questionnaire tools regarding knowledge of pregnant women's nutrition. The results of this study were obtained by using the Chi-Square test, which obtained a p-value = 0,003 (p =<0,005). The conclusion of this study mentioned a correlation between knowledge about the nutrition of pregnant women and chronic energy deficiency in pregnant women in Anuntodea PHC, Tipo. Pregnant women who have good knowledge could prevent the occurrence of CED risks, and the higher the knowledge of the pregnant mother, the lower the CED cases.